Surgical options for Evans-Jensen type IV intertrochanteric femur fractures in the elderly over 65: a comparison between total hip arthroplasty and proximal femoral nail antirotation - Sun, Ming; Liang, Hai-Rui; Zhang, He; Bai, Tong; Xu, Rong-Da; Duan, Si-Yu; Cai, Zhen-Cun (Frontiers in Surgery, 2025)
BackgroundCurrently, there is no clear standard for the surgical options for Evans-Jensen Type IV intertrochanteric femur fractures in elderly patients over 65 years old. This study aims to retrospectively analyze and compare the early postoperative limb function and quality of life of patients treated with total hip arthroplasty (THA) and proximal femoral nail antirotation (PFNA) for this type of fracture. We hypothesize that there is no significant difference in complications and postoperative recovery between the two surgical methods.MethodsA retrospective analysis was conducted on patients over 65 years old with Evans-Jensen Type IV intertrochanteric femur fractures who were treated between 2020 and 2023. The patients were divided into two groups based on the treatment method: the PFNA group (20 cases) and the THA group (20 cases). General patient information, operative time, intraoperative blood loss, time to postoperative mobilization, time to weight-bearing on the affected limb, Harris hip scores at 1, 3, and 6 months postoperatively, excellent and good rates, SF-36 scores, and postoperative complications were recorded.ResultsCompared to the PFNA group, the THA group had a longer operative time (86.7 ± 9.6 vs. 51.5 ± 5.3 min, p < 0.001) and more intraoperative blood loss (212.0 ± 35.5 vs. 76.5 ± 16.1 ml, p < 0.001). However, the THA group had an earlier time to first postoperative mobilization (3.1 ± 1.4 vs. 43.3 ± 13.09 days, p < 0.001) and earlier time to full weight-bearing on the affected limb (33.5 ± 3.1 vs. 77.9 ± 12.0 days, p < 0.001). The Harris hip scores and SF-36 scores at 1, 3, and 6 months postoperatively were higher in the THA group (p < 0.05 for all). There was no significant difference in the overall incidence of postoperative complications between the two groups (p = 0.41).ConclusionFor elderly patients over 65 years old with Evans-Jensen Type IV intertrochanteric femur fractures, especially those with underlying diseases who cannot tolerate prolonged bed rest, hip replacement surgery (THA) may be preferred. Postoperative patients can begin rehabilitation exercises earlier, preventing the exacerbation of internal medical conditions. Early recovery of hip function on the affected side is faster, and the quality of life of patients is higher.